2020
DOI: 10.1042/bsr20194255
|View full text |Cite
|
Sign up to set email alerts
|

Expression profiles and prognostic significance of WNT family members in glioma via bioinformatic analysis

Abstract: Aims: The dysregulation and essential role of WNTs in glioma have been widely implicated. However, there is a paucity of literature on the expression status of all the 19 WNTs in glioma. Our study was aimed to evaluate the expression and prognostic values of the 19 WNTs in glioma. Methods: mRNA expression and clinical data were retrieved from the Cancer Genome Atlas (TCGA) database, Chinese Glioma Genome Atlas (CGGA), GTEx and ONCOMINE databases. The 50 frequent neighbor genes of WNT5A and WNT10B were shown wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 57 publications
0
11
0
Order By: Relevance
“…The expression of WNT5B has been shown in gliomas and atypical teratoid rhabdoid tumors (ATRT), but studies beyond gene expression have not been performed. WNT5B expression was correlated with better overall survival, in contrast to patients with elevated WNT5A expression that had overall worse survival ( Xu et al, 2020 ). In a set of ATRT samples, WNT5B was upregulated in 19 of the 20 samples.…”
Section: Role Of Wnt5b In Cancermentioning
confidence: 99%
“…The expression of WNT5B has been shown in gliomas and atypical teratoid rhabdoid tumors (ATRT), but studies beyond gene expression have not been performed. WNT5B expression was correlated with better overall survival, in contrast to patients with elevated WNT5A expression that had overall worse survival ( Xu et al, 2020 ). In a set of ATRT samples, WNT5B was upregulated in 19 of the 20 samples.…”
Section: Role Of Wnt5b In Cancermentioning
confidence: 99%
“…We found that in females but not males p53 R172H localization is enriched at AP-2gamma DNA-binding motifs. WNT5A has been shown to be upregulated in glioma and is associated with poor overall survival 52 . In our model, Wnt5a mRNA was significantly upregulated in female p53 R172H and down regulated in male p53 R172H .…”
Section: Resultsmentioning
confidence: 99%
“…We evidenced that a very large number of genes involved in gains and shared between TCs and GSCs belong to the GO term cellular component, particularly extracellular space, extracellular region and membrane, indicating a strong involvement in intercellular signaling. Interestingly, several gained genes shared between at least two datasets were reported in the literature as overexpressed in high-grade gliomas, associated with poor prognosis, or in any case, involved in canonical pathways of GBM ( EIF2AK1 , FTL , SRC , GNG8 , GNG11 , GNG7 , FZD9 , GNB2 , TGM2 ) [ 45 , 46 , 47 , 48 , 49 ]. Conversely, only one lost gene, AKR1C2 , shared between at least two datasets, was reported as downregulated and associated with high-risk-score glioma in the REMBRANDT data set [ 50 ].…”
Section: Discussionmentioning
confidence: 99%